Determinants of maternal health care utilization of Pantawid Pamilyang Pilipino Program (4Ps) beneficiaries in Tacloban City - Camposano, Rea Lyn E.; Carvajal, Jeric J.; Riel, John Raphael C.; Pormon, Miah Maye M. (2017)
One of the UN Sustainable Development Goals is to decrease maternal deaths worldwide, specifically in developing countries. In the Philippines, maternal mortality is still increasing due to lack of available health care services. Given this context, the study examined the factors affecting maternal health care utilization among the 93 pregnant and recently delivered 4Ps beneficiaries in the 12 barangays of Tacloban City. Specifically, the paper described the socio-demographic and economic profile, health profile, health care services sought, and the costs incurred among the mothers. Data were collected through personal interviews and key informant interviews with concerned health agencies. There were 38 pregnant and 55 recently delivered mothers, where most of them availed maternal health services such as prenatal and postnatal care, as part of their conditions for the health program of the 4Ps. Two regressions were done. The regressions show that there was a positive correlation on the educational attainment, the presence of chronic disease, and the postnatal care cost of the mother as the individual determinants in availing maternal health care services. However, the societal determinants do not affect the mother's willingness in availing such services. The study recommends the implementing agency to empower the beneficiaries on the benefits and importance of availing maternal health care services.
Undergraduate thesis (BASS Economics) -- University of the Philippines, Tacloban.